A geographic information systems selection approach to repurposing offshore oil & gas assets for green hydrogen production - Rupp, William; Rabea, Karim; Yuan, Ruoyang (Frontiers in Fuels, 2025)
Integrating green hydrogen production with existing oil and gas infrastructure is seen as viable step for the reutilization of oil and gas assets. Green hydrogen production through offshore wind has the potential to extend the lives of these systems, reduce decommissioning costs and provide a source of clean energy. This paper presents an outlook on wind license areas using existing oil and gas infrastructure. Three scenarios are proposed for the conversion of offshore assets into wind turbine sites, including the conversion of a platform into a substation. A methodology is provided to assess the suitability of offshore wind using exclusion criteria and the cessation of production dates for oil and gas infrastructure. This methodology is applied to the UK Exclusive Economic Zone (EEZ), and the results show that 7.4% of the UK EEZ is within the top suitability index for wind turbine development. The cost of green hydrogen production from different offshore locations is estimated to be in the range of 9.78–11.76 £/kgH2 depending on the wind farm scale and the distance. The study highlights the potential for using existing infrastructure for wind turbine development and provides valuable insights for stakeholders in the energy industry.